2011
DOI: 10.2478/s11756-011-0042-1
|View full text |Cite
|
Sign up to set email alerts
|

Small scale gradient effects on isopods (Crustacea: Oniscidea) in karstic sinkholes

Abstract: Abstract:We studied abundance and diversity patterns of terrestrial isopod assemblages along a 'micro-scale' vertical gradient in sinkholes in the Aggtelek National Park, Hungary. Time restricted manual sampling yielded ten native species, including endemic and rare ones. Along the gradient we found no major differences in species richness and -composition, and abundance decreased from the bottoms to the upper zones of the sinkholes. Species specific habitat preference on a vertical gradient showed two distinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 12 publications
0
21
0
1
Order By: Relevance
“…It has been shown that such depressions are refugia for a variety of species (Beck v. Mannagetta 1906;Horvat 1953;Vilisics et al 2011). As our previous studies revealed 2014a), the role of the large and deep forested solution dolines of Hungary in plant species preservation is especially important.…”
Section: Introductionmentioning
confidence: 79%
“…It has been shown that such depressions are refugia for a variety of species (Beck v. Mannagetta 1906;Horvat 1953;Vilisics et al 2011). As our previous studies revealed 2014a), the role of the large and deep forested solution dolines of Hungary in plant species preservation is especially important.…”
Section: Introductionmentioning
confidence: 79%
“…As isolated or semi-isolated cool and humid enclaves, dolines are very important from a nature conservation point of view. It has been shown that such depressions are refugia for a variety of species (Beck v. Mannagetta 1906;Horvat 1953;Vilisics et al 2011). As our previous studies revealed (Bátori et al 2012;2014a), the role of the large and deep forested solution dolines of Hungary in plant species preservation is especially important.…”
Section: Introductionmentioning
confidence: 80%
“…In Bouhedma Park, the small species A. lentus was collected mainly in the first habitat (Bouh 1) and sporadically in the two other habitats (Bouh 2 and 3). In fact, for smaller species, the preferences of microhabitats are satisfied by the existence of small places of shelter, regardless of the general characteristics of the habitat (Vilisics et al 2007(Vilisics et al , 2011. Thus, the small number of captured individuals indicates the scarcity of favorable microhabitats in the Bouhedma Park.…”
Section: Discussionmentioning
confidence: 99%